Mathematical Anxiety in Mathematical Problem Solving: Literature Review - Lala Nailah Zamnah; Kartono Kartono; Rochmad Rochmad; Emi Pujiastuti (International Conference on Science, Education, and Technology, 2021)
Feeling anxious when learning mathematics or things involving mathematics known as math anxiety and problem solving is a process of activities that prioritize the importance of procedures, strategic steps that students take in solving problems, so as to eventually find answers to questions. The purpose of this study was to find out mathematical anxiety in mathematical problem solving. The research method used in this research is a narrative literature review. The result of this narrative literature review is that a person who has mathematical anxiety does not always lead to the failure in solving mathematical problems.